2020
DOI: 10.2478/aoas-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Addition of Probiotic Bacteria (Bacillus Subtilis or Enterococcus faecium) or Phytobiotic Containing Cinnamon Oil to Drinking Water on the Health and Performance of Broiler Chickens

Abstract: The aim of the study was to test whether the use of probiotic bacteria Bacillus subtilis or Enterococcus faecium or a phytobiotic containing cinnamon oil can improve the metabolic parameters, immune status, gut microbiota and histology, and growth performance of broiler chickens. The experiment was carried out on 560 one-day-old male Ross 308 broiler chickens raised until the age of 42 days. The broiler chickens were assigned to 4 experimental groups of 140 birds each (7 replications of 20 individuals each). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
4
17
0
1
Order By: Relevance
“…The fact that this antibiotic has not significantly affected rearing results can be explained by the lack of harmful intestinal bacteria in one-day-old chickens [31]. Krauze et al [14] administered a probiotic containing Bacillus subtilis or E. faecium to chickens throughout the rearing period and noted no effect on production results. In contrast, in our research the use of a probiotic supplement containing E. faecium and B. amyloliquefaciens strains in the drinking water of chickens during the first week of rearing improved growth performance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The fact that this antibiotic has not significantly affected rearing results can be explained by the lack of harmful intestinal bacteria in one-day-old chickens [31]. Krauze et al [14] administered a probiotic containing Bacillus subtilis or E. faecium to chickens throughout the rearing period and noted no effect on production results. In contrast, in our research the use of a probiotic supplement containing E. faecium and B. amyloliquefaciens strains in the drinking water of chickens during the first week of rearing improved growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, on the birds' last day of life, elevated PC levels were not noted in either the small intestinal wall or the blood plasma of chickens receiving either the probiotic or the antibiotic. Literature data show that probiotics exhibit antioxidant activity [14,19,43]. Xue et al [43], in a study on laying hens receiving a probiotic containing B. subtilis strains, found that this supplement had no effect on the PC level in the muscles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations